2005
DOI: 10.1002/ajh.20514
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of blood from patients with sickle cell disease to air changes the morphological, oxygen‐binding, and sickling properties of sickled erythrocytes

Abstract: We collected venous blood samples from 7 steady-state patients with homozygous sickle cell disease under venous oxygen pressure without exposure to air (UnExpblood) and compared the morphological, oxygen-binding, and sickling properties with those of SS cells in aliquots of the same venous blood samples that were oxygenated in room air or at a PO 2 near 180 mmHg (Exp-blood). Results showed that (1) upon deoxygenation under nitrogen, UnExp-blood generated a significantly higher percentage of elongated reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…In response to 5% O 2 - 95% N 2 we found that cells which were exposed to room air during culture did not show sickling or other gross morphological changes (data not shown). This was, in fact, consistent with previous reports [ 28 , 29 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In response to 5% O 2 - 95% N 2 we found that cells which were exposed to room air during culture did not show sickling or other gross morphological changes (data not shown). This was, in fact, consistent with previous reports [ 28 , 29 ].…”
Section: Resultssupporting
confidence: 94%
“…While cells would sickle readily in response to metabisulfite, cells did not sickle in response to low oxygen tension alone. Similar results have been reported previously, including the observation that not all input RBCs will sickle in response to metabisulfite, and molecular results showed the presence of hemoglobin-S (HbS) as the major component of total Hb in cRBCs [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, this is the first study to examine the O 2 transport of human SCD blood mixed with PFC emulsion at physiological temperature, blood pressure, and oxygenation/deoxygenation cycles. Repeated cycles may be of importance since such cycles induce progressive changes in cell shape and function (including O 2 binding) even without additional factors …”
Section: Discussionmentioning
confidence: 99%
“…Repeated cycles may be of importance since such cycles induce progressive changes in cell shape and function (including O 2 binding) even without additional factors. 33 The phenotypic diversity in SCD is widely recognized and there are large differences in clinical severity among patients. 34,35 The reasons for this broad spectrum of clinical manifestations are unclear and may involve factors directly related to O 2 transport, therefore pertinent to our study.…”
Section: Scd Bloodmentioning
confidence: 99%
“…Sickling assays have been developed to give an objective measure of the percentage of circulating cells in a given blood sample that sickle upon exposure to conditions known to cause HbS shift to the T-state, which is prone to polymerize and cause RBC sickling. Traditionally, sickling assays rely on the subjective determination of the percentage of sickling cells by manually counting 200 RBCs through optical microscopy [3, 4, 5, 6]. Therefore, sickling assays based on optical microscopy are cumbersome, time-consuming, and highly observer dependent.…”
Section: Introductionmentioning
confidence: 99%